Tree and Sapling Level Vegetation Analysis in the Social Forestry Area of Nagari Sumpur Kudus, Sijunjung Regency - Marqfirokh, Ramadhana; Chairul (Jurnal Biologi Tropis, 2025)
This research was conducted in the Social Forestry Area of Nagari Sumpur Kudus, from May to October 2023. The reseacrh on this study airns to determine the composition and structure of tree and sapling vegetation in the Social Forestry Area of Nagari Sumpur Kudus, Sijunjung Regency. The method used in this study was a 120-meter transect line with 12 plots. In the plot, sub-plots were made with a size of 10 m x 10 m for the tree level and 5 m x 5 m for the sapling level. The results showed that there were 14 families, 14 genus, 14 species, and 19 individuals at the tree level. The co-dominant families, namely the Cornaceae, Euphorbiaceae, Phyllanthaceae and Ulmaceae. The compotition of sapling level was founds 17 families, 29 genus, 36 species, and 40 individuals. The co-dominant families are in the Phyllanthaceae and Euphorbiaceae. The highest importance index at the tree level was found in the Alangium sp. and the lowest was found in the Dipterocarpus confertus. the highest importance index for sapling level was found in the Cephalomappa malolpticarpa and the lowest was found in the Bischofia javanica and Nephelium cuspidatum. The diversity index (H') for tree-level plants is classified as medium and (H') for sapling-level plants is high.